How to make a cherry pie and see the U.S.A. - Priceman, Marjorie (New York : Alfred A. Knopf, 2008)
Since the Cook Shop is closed, the reader is led around the United States to gather coal, cotton, granite, and other natural resources needed to make the utensils for preparing a cherry pie.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Colored maps on endpapers.
Keywords: Natural resources -- Juvenile fiction; U.S. states -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Baking -- Juvenile fiction; Natural resources -- Fiction; U.S. states -- Fiction; Voyages and travels -- Fiction; Baking -- Fiction; Humorous stories